Flame Retardants - Zafar, Fahmina; Sharmin, Eram (IntechOpen, 2019)
Flame retardants reduce the risk of fire by decreasing the combustion rate and flame propagation in the presence of fire, leading to the prevention and control of fire. Flame Retardants is divided into four sections: section 1 consists of the introduction, section 2 discusses properties, Section 3 comprises nanocomposites, and section 4 includes computational analysis. The book will be useful for scientists and researchers interested in the field of fire control.